Effects of temperature and concentration on rheological behavior of MWCNTs/SiO2(20–80)-SAE40 hybrid nano-lubricant. (August 2016) - Hemmat Esfe, Mohammad; Afrand, Masoud; Yan, Wei-Mon; Yarmand, Hooman; Toghraie, Davood; Dahari, Mahidzal
Abstract: In this work, effects of temperature and solid volume fraction on rheological behaviors of MWCNTs/SiO2 –SAE40 hybrid nano-lubricant were examined. The experiments were performed at the temperatures ranging from 25 °C to 50 °C and solid volume fractions of 0%, 0.0625%, 0.125%, 0.25%, 0.5%, 0.75%, 1%, 1.5% and 2%. Measured results indicated that the nano-lubricant exhibit Newtonian behavior at the solid volume fraction up to 1% and it is non-Newtonian for solid volume fractions of 1.5% and 2%. Viscosity measurements also showed that the viscosity decreases with increasing temperature and rises with an increase in the solid volume fraction. Finally, the empirical correlation with acceptable accuracy has been proposed to predict the dynamic viscosity of MWCNT/SiO2 –SAE40 hybrid nano-lubricants.